Fungsi Hidrologi Kebun Karet (Hevea brasiliensis Muell. Arg) dalam Mereduksi Besaran Curah Hujan Bersih (Hydrological Function of Rubber Plantation (Hevea brasiliensis Muell. Arg) to Reducing the Magnitude of Net Rainfall) - Bejo Slamet; Achmad Siddik Thoha; Riki Jaya Dinata (FORESTA, 2012)
Forest conversion resulted in loss of various forest functions, mainly the hydrological function changes. Mostly of the conversion of forests were to be oil palm and rubber plantations. Rubber plantation although an artificial ecosystem but had the similarity to forest condition. The purpose of this research was to examine the role of rubber plantation to reducing net rainfall that reached the plantation ground through the interception loss mechanism. Water volume balance was used to measure the interception loss.The results showed that the interception on the rubber plantation increased with the increasing of rubber age. Through fall tend to decreased with the increasing of rubber age were 60.56%, 53.62% and 43.79% of the total precipitation for 10 years, 15 years and 25 years of age respectively during the research period. The percentage of stem flow was 5.98% 7.94%, and 4.39% of total precipitation for 10 years, 15 years and 25 years of age respectively. The percentage of interception on rubber plantation for 10 years, 15 years and 25 years were 331.76 mm (19.6%), 428.73 mm (25.3%), and 545.79 mm (51.81%) of the total rainfall (1053.3 mm) respectively. Rubber plantation had good potency to reducing the net rainfall that reached the ground. This condition also informed that rubber plantation could reduce the risk of floods occurrence.Key words: rubber plantation, net rainfall, interception, through fall, stem flow